White Matter Dissection: Lessons from the United Kingdom National Neuroanatomy Undergraduate Competition 2023 - Gardee, Ameerah; Goonewardena, Eranga; Lub, Sytske; Ashraf, Mohammad; Ismahel, Hassan; Chaudhary, Attika; Al-Salloum, Laulwa Nasser; Border, Scott (Asian Journal of Neurosurgery, 2024)
Objective This narrative highlights a student-led initiative that explored white matter dissection techniques within the framework of the National Undergraduate Neuroanatomy Competition 2023.Materials and Methods The project aimed to enhance neuroanatomical education by developing a novel approach to dissection that deviates from the traditional Klingler’s method. Instead, it incorporated contemporary techniques, including diffusion tensor imaging and other radiological tools, to ensure greater anatomical precision and enrich the learning experience.Results The dissections focused on key white matter structures, such as the uncinate fasciculus and the inferior longitudinal fasciculus, and outlined a step-by-step methodology for creating high-quality specimens. These specimens are designed to serve as educational resources, particularly for students with limited access to formal neuroanatomy courses.Conclusion This study emphasizes the critical role of hands-on dissection in neuroanatomy education, showcasing its ability to enhance student engagement, deepen anatomical understanding, and inspire interest in clinical neuroscience careers. By introducing innovative educational tools and methodologies, this initiative makes a meaningful contribution to addressing the issue of “neurophobia” in medical education.
Keywords: dissection; medical education; neuroanatomy; neuroscience; neurosurgery